Simulation of single phase fuel cell powered transformerless multilevel inverter using h-bridge cascaded topology - Nurhafiza Azizan (School of Electrical System Engineering, University Malaysia Perlis, 2014)
This research was discussed about the output voltage waveform of the H-Bridge Cascaded multilevel inverter approaches the pure sine wave simulation. The simulation uses MATLAB software to get the output waveform from fuel cell and the H-Bridge cascaded multilevel inverter topology.